The pros and cons of multiple puncture in percutaneous balloon compression for treatment of trigeminal neuralgia - Sun, Chenglong; Zheng, Wenhao; Zhu, Qiang; Du, Quan; Yu, Wenhua (Frontiers in Neurology, 2022)
Background Percutaneous balloon compression (PBC) is an effective and well-established surgery for treating trigeminal neuralgia (TN). However, if the initial attempt fails to produce a distinct pear shape, there is no conventional strategy to follow: repeat a few days later or re-puncture? Aims This study aimed to analyze the risk and gain of re-puncturation in PBC surgery for TN treatment. Methods We reviewed radiographs and medical records from 79 consecutive PBC cases. The complications and surgical outcomes were compared between one-time success pears and multiple re-puncturing pears. Re-puncturing methods included selecting a more appropriate entry point, a more possible entry angle, finding a stretchy spot around the margin of foramen ovale (FO) with a trocar, and exploring the direction with more resistance using a thinner guiding needle. Results In 50% of cases, satisfactory pears were obtained after the first puncture, and in 35% of cases, satisfactory pears were obtained following re-puncturation. Except for hemihypogeusia, which was significantly more in multiple punctures cases (p < 0.05), no additional adverse effects were statistically different between the two groups. There are very few rare complications associated with re-puncturation. Log-Rank test of pain-free rate revealed no statistically significant differences between the two groups (p = 0.129). Conclusion This study establishes the safety of re-puncturation in PBC surgery for TN treatment. The operation increases pears and does not cause any serious complications. The surgical outcomes of re-puncturation pears are almost identical to those one-time success pears.